The important chapter of class 10th Pair of linear equations in two variables how i solve the question by both method Solve the following pair of linear equations by the elimination method and the substitution method:(iv) x/2+ 2y/3 = -1 and x-y/3 = 3

AnilSinghBoraGuru

# Solve the following pair of linear equations by the elimination method and the substitution method:(iv) x/2+ 2y/3 = -1 and x-y/3 = 3 Q.1(4)

Share

By the method of Elimination.

3x + 4y = -6 â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦. (i)

x-y/3 = 3

3x â€“ y = 9 â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦. (ii)

When the equation (ii) is subtracted from equation (i) we get,

-5y = -15

y = 3 â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦.(iii)

When the equation (iii) is substituted in (i) we get,

3x â€“ 12 = -6

3x = 6

x = 2

Hence, x = 2 , y = -3

By the method of Substitution:

From the equation (ii) we get,

x = (y+9)/3â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦â€¦(v)

Putting the value obtained from equation (v) in equation (i) we get,

3(y+9)/3 +4y =âˆ’6

5y = -15

y = -3

When y = -3 is substituted in equation (v) we get,

x = (-3+9)/3 = 2

Therefore, x = 2 and y = -3